STUDY OF THE PREVALENCE OF TUBERCULOSIS AND THE MANAGEMENT OF PATIENTS IN THE KASUKU II HEALTH CENTER IN THE KINDU HEALTH ZONE; STUDY CONDUCTED OVER A BIENNIAL PERIOD 2022-2023. - Louis Odiko Ndjate; Matisho Morisho Evelyne; Et Yves Kaleba Yengo (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING)
More than 95% of deaths from tuberculosis occur in developing countries, but tuberculosis remains a public health problem because it is an infectious disease that most commonly affects the lungs caused by a type of bacteria that spreads through the body. Air when infected people cough, sneeze or spit. To this we asked ourselves the following question: what is the prevalence of TUBERCULOSIS and the ratio of PEC in AS KASUKU II for the period under review? Our overall objective is to determine the prevalence rate of TB in the KASUKU II Health Area. In our study which was cross-sectional and prospective; we used the documentary method and the technique of face-to-face interviews with the staff of this health structure and found the following results: Out of a total of 5036 cases consulted during this period, 252 were affected by diagnosed tuberculosis clinically or bacteriologically, a prevalence rate of 5%; males with 61.9% of cases, i.e. a female-male sex ratio of 1.62 and the age group between 15 and 54 years old had a rate of 64.68%. The following therapeutic results were found: among the 252 people treated in this health structure, 86.5% had completed the treatment; 99.08% were clinically and bacteriologically declared cured; 0.91% experienced a relapse; 11.9% were undergoing treatment; 0.39% death cases; 1.19% were lost to follow-up. Considering these results, we came to the conclusion that the prevalence of tuberculosis in this SA is high and is close to that published by the WHO throughout the world and also to that of the 2012-2013 DHS and the treatment starting from the therapeutic data found, certifies that it is acceptable.